Transformation of sperm structure in Octopus vulgaris: From spermatogenesis to spermatophoric release - Hyeon Jin Kim; Jung Jun Park; Jung Sick Lee (PLoS ONE, 2025)
The present study describes the differentiation process of male germ cells in Octopus vulgaris, the morphology of sperm in the testis and spermatophore, and the sperm released after the spermatophoric reaction. During spermatogenesis, the male sperm cell gradually elongates from a round shape, with cytoplasm shifting toward the head and the acrosome forming. Additionally, in the spermatid stage, the flagellum develops within the posterior nuclear channel and extends outside the cytoplasm. The sperm is composed of a head and a tail. The head is approximately 17.9 μm long and consists of a highly electron-dense nucleus and a helical acrosome. The tail is divided into three parts: the mid-piece, principal-piece, and end-piece. The mid-piece forms a mitochondrial sheath with 7–8 mitochondria surrounding a “9+2” axoneme. The principal-piece is composed of an axoneme, outer dense fibers, and fibrous sheath, while the end piece lacks outer dense fibers or fibrous sheath. The sperm in the testis and spermatophore, and the sperm released after the spermatophoric reaction have the same structure. However, in the sperm located in the testis and spermatophore, the structure of the acrosome is unclear due to the presence of cytoplasm in the head. In contrast, sperm released after the spermatophoric reaction lack their cytoplasm, revealing the helical acrosome. This unique sperm morphology, adapted for internal fertilization, is thought to be advantageous for fertilization and long-term storage within the female reproductive system.